Serum Autotaxin Is a Useful Disease Progression Marker in Patients with Primary Biliary Cholangitis - Satoru Joshita (Nature Portfolio, 2018)
Abstract Autotaxin (ATX) is a secreted enzyme metabolized by liver sinusoidal endothelial cells that has been associated with liver fibrosis. We evaluated serum ATX values in 128 treatment-naïve, histologically assessed primary biliary cholangitis (PBC) patients and 80 healthy controls for comparisons of clinical parameters in a case-control study. The median ATX concentrations in controls and PBC patients of Nakanuma’s stage I, II, III, and IV were 0.70, 0.80, 0.87, 1.03, and 1.70 mg/L, respectively, which increased significantly with disease stage (r = 0.53, P < 0.0001) as confirmed by Scheuer’s classification (r = 0.43, P < 0.0001). ATX correlated with Wisteria floribunda agglutinin-positive Mac-2 binding protein (M2BPGi) (r = 0.51, P < 0.0001) and fibrosis index based on four factors (FIB-4) index (r = 0.51, P < 0.0001). While ALP and M2BPGi levels had decreased significantly (both P < 0.001) by 12 months of ursodeoxycholic acid treatment, ATX had not (0.95 to 0.96 mg/L) (P = 0.07). We observed in a longitudinal study that ATX increased significantly (P < 0.00001) over 18 years in an independent group of 29 patients. Patients succumbing to disease-related death showed a significantly higher ATX increase rate (0.05 mg/L/year) than did survivors (0.02 mg/L/year) (P < 0.01). ATX therefore appears useful for assessing disease stage and prognosis in PBC.